Pengaruh pengalaman mengajar dan motivasi mengajar terhadap profesionalisme guru taman kanak-kanak se-kecamatan Way Jepara - Wiranti, Reni (Jurnal Humaniora dan Ilmu Pendidikan, 2021)
Purpose: This study aimed to understand the impact of teaching experience on teacher professionalism, the impact of teaching motivation on teacher professionalism, and the effect of teaching experience and teaching motivation on teaching professionalism. Research methodology: This research used a quantitative approach. The data analysis techniques used were descriptive analysis, prerequisite test; and hypothesis test. Results: The results show; 1) there is a significant influence between teaching experience on teacher professionalism and coefficient of determination teacher experience as much as 33.6% of teacher professionalism, 2) there is a significant influence between teaching motivation on teacher professionalism and determination coefficient of teacher experience as much as 57.9% of teacher professionalism; (3) teaching experience and teaching motivation significantly influence the professionalism of teachers with the influence of simultaneously variable teaching experience and teaching motivation to teacher professionalism as much as 61.7%. Limitations: The data were only collected through interviews. Contribution: The results of this study can be used to evaluate the effectiveness of the implementation of education programs on improving teacher professionalism.